An American procession - Kazin, Alfred 1915-1998 (Knopf, 1984)
A study of the major American writers from the 1830's to the 1930's.
Keywords: Geschichte 1830-1930; Geschichte 1830-1932; Geschichte 1820-1929; Littérature américaine - Histoire et critique; American literature -- History and criticism; Literatur; USA